Animalia: Animals in the Archives, Archives of Ontario - Grant, Jennifer (Archivaria, 2019)
Animalia: Animals in the Archives. Helen McClung Exhibit Area, Archives of Ontario, Toronto, Ontario. December 2018 (ongoing). Curated by Jay Young.